APPLICATION OF THE EXAMPLE NON-EXAMPLE METHOD TO IMPROVE SOCIAL SCIENCE (IPS) LEARNING OUTCOMES IN ECONOMIC ACTIVITY LEARNING MATERIAL AT GRADE 5 OF SD KRISTEN 03 EBEN HAEZER SALATIGA - Afandi Roqit; Krisma Widi Wardani (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
Example Non Example is applied to improve the fifth-grade students’ learning outcomes at Eben Haezer Salatiga Christian Elementary School 03. The research used a classroom action research approach, which was conducted in 2 cycles. The research involved 26 students in class 5C of SD Kristen 03 Eben Haezer Salatiga. Data collection included posttest scores for each cycle to test the effectiveness of the Example Non Example method in improving social science learning outcomes for students in class 5C. In addition, an observation sheet was also used to observe the activities of teachers and students in the application of the Example Non-Example method. The research results indicate that an increasing value of the number of students who achieved learning completeness initially from 11 students (42.31%) increased to 18 students (69.23%) in cycle I, and subsequently increased to 23 students (88.46%) in cycle II. The application of the Example Non-Example method succeeded to improve learning outcomes and achieved indicator completeness, which was 88% of students who reached learning completeness. Hence, it can be concluded that applying the Example Non-Example method can improve 5C students’ learning outcomes at Eben Haezer Salatiga Christian Elementary School 03